1997
DOI: 10.1159/000239578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Midazolam on the Differentiation of Murine Myeloid Leukemia Cells

Abstract: The effects of midazolam (MID) on the in vitro growth and differentiation of two murine myeloid leukemia WEHI 3B (JCS) and M1 cells were studied. MID inhibits the proliferation of both Ml and JCS cells in a dose-dependent manner. At the concentration of 10 μg/ml, MID was found to induce both monocytic and granulocytic differentiation of the JCS but not Ml cells. Induction of morphological differentiation of the JCS cells was also associated with the enhanced expression of the differentiation antigens Mac-1, F4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…This cell line has been widely used to be a useful model in the study of hematopoietic cell differentiation [2–4, 32, 33]. In the present study, we have demonstrated that rSj16 could induce macrophage differentiation of the WEHI-3B JCS cell (Figures 3–5).…”
Section: Discussionsupporting
confidence: 65%
“…This cell line has been widely used to be a useful model in the study of hematopoietic cell differentiation [2–4, 32, 33]. In the present study, we have demonstrated that rSj16 could induce macrophage differentiation of the WEHI-3B JCS cell (Figures 3–5).…”
Section: Discussionsupporting
confidence: 65%
“…Midazolam has been shown to inhibit the in vitro growth and differentiation of two murine myeloid leukemia cell lines (WEHI 3B (JCS) and M1 cells) in a dose-dependent manner [28]. Midazolam enhanced the expression of the differentiation antigens Mac-1, F4/80, and Gr-1 in the cells and expression of tumor necrosis factor (TNF-alpha), and the neutrophil-specific J11d differentiation marker was significantly upregulated in midazolam-treated JCS cells.…”
Section: Resultsmentioning
confidence: 99%